2020
DOI: 10.3758/s13415-020-00782-9
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of inflammation, neurobiology, and cognitive function in PTSD: an integrative review

Abstract: Compelling evidence from animal and human research suggest a strong link between inflammation and posttraumatic stress disorder (PTSD). Furthermore, recent findings support compromised neurocognitive function as a key feature of PTSD, particularly with deficits in attention and processing speed, executive function, and memory. These cognitive domains are supported by brain structures and neural pathways that are disrupted in PTSD and which are implicated in fear learning and extinction processes. The disruptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 346 publications
(389 reference statements)
0
34
0
1
Order By: Relevance
“…All other trauma types' negative impact on EF is indirect, via its mental health impact (e.g., PTSD, depression, and anxiety) (Kira et al, 2020, b, c, d, e, f;Kira et al, 2021). The impact of PTSD, depression, and anxiety on cognition and executive functions is welldocumented (Esterman et al, 2019;Liu et al, 2019; for reviews and meta-analyses for PTSD see Woon et al, 2017; see also, Aupperle et al, 2012;Quinones et al, 2020; for depression see McDermott & Ebmeier, 2009; see also Airaksinen et al, 2004; for anxiety see Gulpers et al, 2016;Moran, 2016;Shi et al, 2019). Post-trauma alterations in neurocognitive functioning are likely to reflect changes in underlying brain networks predictive of PTSD, depression, and anxiety (e.g., Messina et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…All other trauma types' negative impact on EF is indirect, via its mental health impact (e.g., PTSD, depression, and anxiety) (Kira et al, 2020, b, c, d, e, f;Kira et al, 2021). The impact of PTSD, depression, and anxiety on cognition and executive functions is welldocumented (Esterman et al, 2019;Liu et al, 2019; for reviews and meta-analyses for PTSD see Woon et al, 2017; see also, Aupperle et al, 2012;Quinones et al, 2020; for depression see McDermott & Ebmeier, 2009; see also Airaksinen et al, 2004; for anxiety see Gulpers et al, 2016;Moran, 2016;Shi et al, 2019). Post-trauma alterations in neurocognitive functioning are likely to reflect changes in underlying brain networks predictive of PTSD, depression, and anxiety (e.g., Messina et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These results are supported by Positron Emission Tomography (PET) scans in PTSD patients [28]. Based on their anxiolytic effects, selective serotonin reuptake inhibitors (SSRIs) are recommended as second-line treatment, being effective in decreasing hyperarousal symptoms of PTSD (irritability, anger, depression) but having little effect on hypoarousal symptoms [6,19]. When administered shortly after exposure to trauma, SSRIs -escitalopram, showed promising response in acute reduction of PTSD symptoms [29].…”
Section: Discussionmentioning
confidence: 92%
“…Several studies have demonstrated the linkage between the dysregulation of the HPA axis and PTSD onset, mainly throughout the low levels of cortisol secretion, which further points to vulnerability to develop PTSD [19,20]. In addition to glucocorticoid's ability to modulate the stress PFC -prefrontal cortex; Ht -hypothalamus; Nac -nucleus accumbens; Hc -hippocampus; A -amygdala; The orange, yellow and red arrows represent the monoaminergic pathways/ projections (red -norepinephrine, orange -serotonine and yellow -dopamine).…”
Section: Discussionmentioning
confidence: 99%
“…Given the cognitive dysfunction is also considered as the combined symptom associated with PTSD [ 18 ], we further tested the learning and memory ability with Morris water maze. In acquisition task, which aimed to test the spatial learning of the mice, PTSD mice displayed the dramatic prolonged escaping time to position the hidden platform ( Figure 3A , two-way ANOVA, Tukey’s post-hoc test, PSTD vs. control: p < 0.001 on Day 2, Day 3 and Day 4).…”
Section: Resultsmentioning
confidence: 99%